War-related penile injuries in Libya: Single-institution experience - Abdalla M. Etabbal (Taylor & Francis Group, 2018)
Objective: To report on our initial experience in the management of war-related penile injuries; proper diagnosis and immediate treatment of penile injuries is essential to gain satisfactory results. Besides treating primary wounds and restoring penile function, the cosmetic result is also an important issue for the surgeon. Patients and methods: The study was conducted in the Department of Urology at Benghazi Medical Center and comprised all patients who presented with a shotgun, gunshot or explosive penile injury between February 2011 and August 2017. The patient’s age, cause of injury, site and severity of injuries, management, postoperative complications, and hospital stay, were recorded. Results: In all, 29 males with war-related penile injuries were enrolled in the study. The mean (SD) age of these patients was 31.3 (10.5) years. The glans, urethra, and corporal bodies were involved in four (13.7%), 10 (34.4%), and 20 (68.9%) of the patients, respectively. According to the American Association for the Surgery of Trauma Penis Injury Scale, Grade III penile injuries were the most common (11 patients, 37.9%). The most common post-intervention complications were urethral stricture with or without proximal urethrocutaneous fistula (eight patients, 27.5%), followed by permanent erectile dysfunction (five patients, 17.2%). Conclusion: In patients who sustain war-related penile injuries the surgeon’s efforts should not only be directed to restoring normal voiding and erectile function but also on the cosmetic appearance of the penis.